Реафирмација на регионалниот економски развој: современи трендови за подобрување на ефикасноста на стратегиите и политиките - Цветановска Гугоска, Билјана (Економски факултет, УКИМ, Скопје, 2016)
In the context of globalization and dynamic economic processes regions seem to gain crucial importance in the course of development. The increasing emphasis being placed on the role of regions raised significant changes in the theoretical approaches used in defining regional economic development and in the ways theories might be used to improve policies and strategies. Immaterial factors such as social capital, trust, leadership, networking, partnerships etc. have become essential part of the contemporary regional economic development. Subsequently, the new regional policies and strategies have been transformed into more context sensitive policies which tend to stimulate local communities to be proactive toward sustainable development and their own economic, social and political future. Nine years after the establishment of the balanced regional development policy and in light of the current trends in regional economic development and regional policies, the Republic of Macedonia faces new challenges. The policy which was initially inspired by the political idealism, entrenched in the principles for economic and social equality of the European Union, now needs to be reassessed. Instead of being only redistributive policy targeting interventions mostly in less-developed regions, it must focus on growth and development of all regions using social capital and mobilizing local potential.
Reaffirmation of regional economic development: contemporary trends for efficiency improvement of the strategies and policies
Докторска дисертација одбранета во 2016 година на Економскиот факултет во Скопје, под менторство на проф. д–р Наталија Николовска.
Keywords: contemporary regional development, regional development policy, immaterial development factors, innovstion, networking, social capital, Republic of Macedonia